Deceptive feminist : the failure of feminism in Salman Rushdie’s fiction - Norjahan Makmon (2010)
Salman Rushdie, by his own admission, has “repeatedly sought to create female characters as rich and powerful as those [he has] known”. Women are crucial to Rushdie’s novels Shame, The Enchantress of Florence and The Ground Beneath Her Feet. The women of these novels are shown to resist the conventional expectations that are placed upon them, yet for all the disturbances that they cause to their respective social dynamics, they ultimately fail to display positive feminist qualities.